A suitable RNA preparation methodology for whole transcriptome shotgun sequencing harvested from Plasmodium vivax-infected patients - Catarina Bourgard (Nature Portfolio, 2021)
Abstract Plasmodium vivax is a world-threatening human malaria parasite, whose biology remains elusive. The unavailability of in vitro culture, and the difficulties in getting a high number of pure parasites makes RNA isolation in quantity and quality a challenge. Here, a methodological outline for RNA-seq from P. vivax isolates with low parasitemia is presented, combining parasite maturation and enrichment with efficient RNA extraction, yielding ~ 100 pg.µL−1 of RNA, suitable for SMART-Seq Ultra-Low Input RNA library and Illumina sequencing. Unbiased coding transcriptome of ~ 4 M reads was achieved for four patient isolates with ~ 51% of transcripts mapped to the P. vivax P01 reference genome, presenting heterogeneous profiles of expression among individual isolates. Amongst the most transcribed genes in all isolates, a parasite-staged mixed repertoire of conserved parasite metabolic, membrane and exported proteins was observed. Still, a quarter of transcribed genes remain functionally uncharacterized. In parallel, a P. falciparum Brazilian isolate was also analyzed and 57% of its transcripts mapped against IT genome. Comparison of transcriptomes of the two species revealed a common trophozoite-staged expression profile, with several homologous genes being expressed. Collectively, these results will positively impact vivax research improving knowledge of P. vivax biology.